Anticipated nursing care: findings from a qualitative study - Michela Bottega; Alvisa Palese (BMC, 2020)
Abstract Background Contrary to Missed Nursing Care, some anecdotal data and sparse evidence has documented the tendency of nurses to anticipate some nursing interventions. However, no study has been conducted to date with the purpose of understanding this phenomenon and its underlying mechanisms and consequences. The aim of this study was to describe the phenomenon of delivering anticipated nursing care, its antecedents and consequences as perceived by nurses. Method A descriptive qualitative study. The Consolidated Criteria for Reporting Qualitative Research guidelines were followed. A purposeful sample of 17 clinical nurses and nurse managers working in three Italian hospitals were interviewed in depth in 2019. The audio-recorded interviews were verbatim transcribed and thematically analysed. Results 'Anticipated Nursing Care' is delivered significantly earlier than when expected by nurses in their care plan, by patients, by caregivers and by other members of the team. Medication administration, mobilisation of patients, hygiene care, changes of dressing, vital parameter monitoring, blood sampling and administrative activities were reported as interventions delivered before rather than when expected. Clinically stable patients have been reported to be at risk of receiving anticipated nursing care. Individual values and attitudes, group attitudes of being always ready for the "unexpected", implicit group norms to "leave the patients and the unit in order", high workloads, intertwined activities and work processes inside the units, have been reported as reasons for Anticipated Nursing Care. Effects of this phenomenon have been reported at the patients' and at the nurses' level. Conclusion Anticipated Nursing Care occurs when nurses perform interventions earlier than expected according to an implicit or explicit decision and not as a consequence of a request. The phenomenon requires future studies to detect its diffusion and to accumulate evidence. Its presence in daily practice, if confirmed, suggests that Missed Nursing Care studies should also consider the combined effect of these two phenomena as, on one hand, there may be the tendency to postpone and, on the other hand, the tendency to anticipate interventions.